A study on customer satisfaction toward service quality at Bank Rakyat Beaufort branch / Mohd Nurul Iman Mat Saad - Mat Saad, Mohd Nurul Iman (2010)
This study will conduct in Bank Rakyat Beaufort branch at Sabah. Bank Rakyat Beaufort branch has seen the service quality as one of the crucial element in their business. Bank Rakyat Beaufort branch believe that satisfying their customers may help them to make sure that their will keep performing in the market. Bank Rakyat Beaufort branch main objective of their strategy is to make sure that their customer are satisfy with their service, and they believe that satisfied customer will loyal to Bank Rakyat Beaufort branch and keep on using their service. In order to achieve this, Bank Rakyat Beaufort branch has continuously develop their quality from time to time and they will continue develop this model to promote quality service to their customer. This research will use the quantitative data, whereby 120 questionnaires will distributed and will be analyze. The main focus of this research is to evaluate the customer satisfaction on the service quality of Bank Rakyat Beaufort branch.